A Comparative Study on Marble Dust as a Replacement Agent on Cement Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
White Marble has been used as a material since from the past. The marble dust which is the residue of  marble is very harmful and it needs good disposal efforts. Marble dust is a waste product formed during the production  of marble about 25% of the original marble mass is lost in  the form of dust. The highlights incorporated in this paper is  that how we can use marble dust as a replacement agent. Use  of marble dust as a replacement for fine aggregate in concrete  is investigated. Marble has replaced fine aggregate at content  levels of 0, 4, 8, 12, and 16 in concrete. Five different series  of concrete mixtures were designed to investigate the various  properties on Marble dust concrete. Gradual reduction in  compressive strength was observed with the increase in the  percentage of Marble dust. It also concludes that up to 4% of  Marble slurry can be added into concrete mixes without  considerable reduction in strength of concrete. Percentage of  water absorption decreases as the % of marble aggregate  increases. The objective of the study was to study the effect  of partial replacement of fine aggregates with rubber  aggregates on different percentages of Marble Dust  aggregates to M25 mix. Utilization of Marble dust  aggregates, which is a waste product, in concrete  construction is economically viable and environmentally  effective. The present work is based on the effect of addition  of marble dust in Portland cement concrete.
Keywords: Marble dust; Replacement agent; Cement concrete; Flexural strength